Coastal Erosion of Permafrost Soils Along the Yukon Coastal Plain and Fluxes of Organic Carbon to the Canadian Beaufort Sea. Issue 2 (17th February 2018) - Couture, Nicole J.; Irrgang, Anna; Pollard, Wayne; Lantuit, Hugues; Fritz, Michael
Abstract: Reducing uncertainties about carbon cycling is important in the Arctic where rapid environmental changes contribute to enhanced mobilization of carbon. Here we quantify soil organic carbon (SOC) contents of permafrost soils along the Yukon Coastal Plain and determine the annual fluxes from coastal erosion. Different terrain units were assessed based on surficial geology, morphology, and ground ice conditions. To account for the volume of wedge ice and massive ice in a unit, SOC contents were reduced by 19% and sediment contents by 16%. The SOC content in a 1 m 2 column of soil varied according to the height of the bluff, ranging from 30 to 662 kg, with a mean value of 183 kg. Forty‐four per cent of the SOC was within the top 1 m of soil and values varied based on surficial materials, ranging from 30 to 53 kg C/m 3, with a mean of 41 kg. Eighty per cent of the shoreline was erosive with a mean annual rate of change of −0.7 m/yr. This resulted in a SOC flux per meter of shoreline of 132 kg C/m/yr, and a total flux for the entire 282 km of the Yukon coast of 35.5 × 10 6 kg C/yr (0.036 Tg C/yr). The mean flux of sediment per meter of shoreline was 5.3 × 10 3 kg/m/yr, with a total flux of 1, 832 × 10 6 kg/yr (1.832 Tg/yr). Sedimentation rates indicate that approximately 13% of the eroded carbon was sequestered in nearshore sediments, where the overwhelming majority of organic carbon was of terrestrial origin. Plain Language Summary: The oceans help slow the buildup of carbon dioxide (CO2 ) because they absorb much of this greenhouse gas. However, if carbon from other sources is added to the oceans, it can affect their ability to absorb atmospheric CO2 . Our study examines the organic carbon added to the Canadian Beaufort Sea from eroding permafrost along the Yukon coast, a region quite vulnerable to erosion. Understanding carbon cycling in this area is important because environmental changes in the Arctic such as longer open water seasons, rising sea levels, and warmer air, water and soil temperatures are likely to increase coastal erosion and, thus, carbon fluxes to the sea. We measured the carbon in different types of permafrost soils and applied corrections to account for the volume taken up by various types of ground ice. By determining how quickly the shoreline is eroding, we assessed how much organic carbon is being transferred to the ocean each year. Our results show that 36 × 10 6 kg of carbon is added annually from this section of the coast. If we extrapolate these results to other coastal areas along the Canadian Beaufort Sea, the flux of organic carbon is nearly 3 times what was previously thought. Key Points: Eroding permafrost along the Yukon coast contributes 0.036 Tg of soil organic carbon to the Beaufort Sea annually In permafrost soils, large corrections to organic carbon contents are needed to properly account for the volume of ground ice More than half of the soil organic carbon in coastal bluffs is found at depths greater than 1 m